Southern and postcolonial perspectives on policing, security and social order - Cavalcanti, Roxana Pessoa; Squires, Peter; Waseem, Zoha (Bristol University Press, 2025)
Postcolonial legacies continue to impact upon the Global South and this edited collection explores their influence on systems of policing and social ordering. Expanding the Southern criminology agenda, the book critically examines social and environmental harms, violence and war crimes, human rights abuses and the criminalisation of protest.